Insecticide Spray Guide for the Control of Spodoptera Frugiperda JE Smith (Lepidoptera: Noctuidae) basing on Maize Crop Injury Signs - Mbemba, Kiva F; Rwegasira, Gration M; Tryphone, G. M. (Discoveries in Agriculture and Food Sciences, 2024)
Fall armyworm, Spodoptera frugiperda (J. E. Smith), is a polyphagous migratory pest that attacks more than 353 plant species among which are major crops in Africa. Farmers have been opting for insecticide-based control despite the lack of clear guides on the suitable insecticides and right timing for application. Farmers respond to S. frugiperda through injury signs inflicted on maize crop but it’s less known how effective is the injury signs-based decisions. This study aimed at establishing the right choice of insecticides and timing of application based on crop injury signs. Ten farmer-preferred insecticides were used against S. frugiperda on damaged maize crop in the field. Obtained results suggested that injury sign based application of insecticides has significant (p < 0.001) effect on mortality of S. frugiperda larvae. Ninja plus 5EC, Profecron 720 EC, Multi alpha plus 150 EC and Duduba 450 EC, caused highest mortality of S. frugiperda in all experiments while Thunder 145 OD and Attakan 350 SC were the least effective. The obtained yields suggested a significant impact of applied insecticides whereby plots treated with Duduba 450 EC produced highest yield (4tons/ha) compared to non-treated plot (2.2 tons/ha). The findings from this study proves for the first time that S. frugiperda can be effectively managed through tallying of insecticide spray with injury signs manifested on maize crop. The developed insecticides advisory spray guide should be recommended as S. frugiperda field management option which is easily understandable by the farmers.